Artificial Intelligence Integration to Improve the Effectiveness of Digital Education - Michael Andre Collins; Sarah Elizabeth Thompson (Innovate Inovation Teaching And Learning, 2025)
This study aims to analyze the integration of artificial intelligence (AI) in Indonesia's education system and its impact on learning quality, personalized education, and inclusiveness. Using a mixed-method approach, data were collected from literature reviews, interviews, and surveys of educators, students, and policymakers. The findings indicate that AI implementation can enhance the efficiency of teaching and learning processes, support adaptive learning, and expand access to education across various regions. The success of this integration depends heavily on digital infrastructure readiness, teachers' competencies, and supportive policies for technological innovation. Additionally, ethical considerations and data privacy are critical to ensuring responsible AI deployment. The results emphasize that collaboration among government, educational institutions, and technology developers is essential to accelerate the digital transformation of education. Key recommendations include increasing teacher training, strengthening AI ethical regulations, and developing equitable infrastructure to achieve inclusive and high-quality education in Indonesia